GENOTYPIC RESPONSE TO MATURED EMBRYO-DERIVED CALLUS INDUCTION AND PLANT REGENERATION IN HIGH YIELDING UPLAND RICE (Oryza sativa L.) (Applied Biological Research, 2023)
An efficient and reproducible protocol is required to achieve high frequency  transformation from transformed calli. In this paper, high frequency plant  regeneration from mature embryo-derived embryogenic calli of recalcitrant  indica rice cultivars (‘Khandagiri’, ‘Sahbhagidhan’ and ‘Mandakini’) is  reported. Maximum frequency of embryogenic and nodular callus (73.5%)  followed by plant regeneration (88.5%) was obtained in cv. ‘Khandairi’.  Further, ‘Sahbhagidhan’ (82.3%) and ‘N22 Sel’ (75.3%) showed higher organogenic plantlet regeneration than ‘Mandakini’ (70.8%), but reverse  was the case for somatic embryogenic plant regeneration. Rice cv. ‘Annada’ and ‘Vandana’ exhibited poor organogenic and somatic embryogenic  callusing and plantlet regeneration response. Therefore, organogenic and  somatic embryogenic plant regeneration have their own genetic basis and  these two phenomena might be under separate genetic control in various  genotypes. The present high throughput plant regeneration system can be  amenable for genetic improvement through in vitro mutagenesis and  Agrobacterium-mediated genetic transformation in upland rice.
Keywords: Callus induction; genotypic response; Oryza sativa; plant regeneration; mature embryo